2010
DOI: 10.1007/s10633-010-9220-7
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of generalized retinal function and progression of maculopathy after cessation of therapy in a case of severe hydroxychloroquine retinopathy with 19 years follow-up

Abstract: A 40-year-old Caucasian female was first seen 20 years ago for a routine ocular screening in relation to hydroxychloroquine treatment for systemic lupus erythematosus. Her daily dose was 600 mg (or 12 mg/kg of body weight/day) of hydroxychloroquine. Three years later, she complained of mild visual loss in the right eye. Her best-corrected visual acuity was 0.9 in the right (RE) and 1.0 in the left eye (LE). In addition, she had a central scotoma (RE > LE) on automated visual field analysis (Humphrey central 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Nevertheless, there is high variability in the cumulative doses that lead to toxic retinopathy [ 11 ] and the damage may appear even in those patients with a low systemic risk profile. Also, a high risk of progression of the retinal damage has been suggested despite the cessation of the treatment [ 12 ] and a “point of no return” for macular toxicity [ 13 ]. Thus, an individual and weight-adapted dosing has been proposed to minimize the incidence of retinal damage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is high variability in the cumulative doses that lead to toxic retinopathy [ 11 ] and the damage may appear even in those patients with a low systemic risk profile. Also, a high risk of progression of the retinal damage has been suggested despite the cessation of the treatment [ 12 ] and a “point of no return” for macular toxicity [ 13 ]. Thus, an individual and weight-adapted dosing has been proposed to minimize the incidence of retinal damage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Given the infrequent occurrence of toxic effects, few data are available on the presenting features and long-term follow-up of patients with hydroxychloroquine retinopathy, making it difficult to surmise the clinical course of patients after cessation of drug treatment. 6,[9][10][11][12][13] Yam and Kwok 5 speculated that toxic effects could be separated into premaculopathy and true retinopathy, with the opportunity for reversibility if changes are detected in the former stage. The most characteristic imaging features of hydroxychloroquine toxic effects include disruption of normal FAF, whereas on SD-OCT there is RPE atrophy and loss of the photoreceptor layer.…”
mentioning
confidence: 99%
“…photopic and mesopic conditions in a patient with SLE with HCQ retinopathy. The results of the patient were compared with 10 healthy people in the same age group and were found to be signi cantly lower than the healthy group at all spatial frequencies (24). Bishara et al reported high frequency of pathological and suspicious contrast sensitivity tests in the medication group (25).…”
Section: Discussionmentioning
confidence: 98%